2015
DOI: 10.1002/ejsp.2126
|View full text |Cite
|
Sign up to set email alerts
|

Exploring patterns of explicit and implicit anti‐gay attitudes in Muslims and Atheists

Abstract: Research into the relationship between religion and anti-gay attitudes frequently focuses on Christianity. We explored the role of religiosity dimensions, previous contact, and factors in the dual-process motivation model as predictors of explicit and implicit anti-gay attitudes in samples of Muslims and Atheists. The explicit and implicit attitudes of Muslims were more negative than the attitudes of Atheists. Explicit attitudes were more negative towards gay men than lesbians; implicit attitudes were negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
33
1
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(44 citation statements)
references
References 62 publications
(130 reference statements)
5
33
1
5
Order By: Relevance
“…Anderson et al (2015) found that this relationship exists after statistically controlling for the variables in the DPM, and in fact macro justice explains approximately equal amounts of variance as RWA (albeit in different directions). Anderson et al (2015) found that this relationship exists after statistically controlling for the variables in the DPM, and in fact macro justice explains approximately equal amounts of variance as RWA (albeit in different directions).…”
Section: Ideological Variables and Attitudesmentioning
confidence: 86%
See 3 more Smart Citations
“…Anderson et al (2015) found that this relationship exists after statistically controlling for the variables in the DPM, and in fact macro justice explains approximately equal amounts of variance as RWA (albeit in different directions). Anderson et al (2015) found that this relationship exists after statistically controlling for the variables in the DPM, and in fact macro justice explains approximately equal amounts of variance as RWA (albeit in different directions).…”
Section: Ideological Variables and Attitudesmentioning
confidence: 86%
“…J. Indeed, there is evidence from research into other prejudices that religiosity (i.e., individual differences in religion) is more important than religious affiliation (i.e., self-identified social category; Anderson & Koc, 2015;Whitley, 2009). Although Perry and colleagues reported that Christians were more negative towards asylum seekers than non-Christians, they also revealed a suppression effect to the extent that the positive attitudes of Christians in their sample were being attenuated because of an internal conflict with high levels of authoritarianism.…”
Section: Demographic Variables and Attitudesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, attitudes towards gay men have remained quite negative in Turkey, despite improvements in other western nations (Anderson & Koc, 2015;Sakalli, 2002), and LGBT people continue to experience direct and indirect forms of discrimination in access to education, employment and health care (Gocmen & Yilmaz, 2017). Dominant cultural conceptions of manhood in Turkey, also echoed by gay men themselves, maintained the importance of masculinity and the rejection of femininity (Bolak-Boratav, Fisek, & Ziya, 2014;Erol & Ozbay, 2013).…”
mentioning
confidence: 99%